2022
DOI: 10.1186/s13046-022-02242-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide CRISPR/Cas9 library screen identifies PCMT1 as a critical driver of ovarian cancer metastasis

Abstract: Background The development of lethal cancer metastasis depends on the dynamic interactions between cancer cells and the tumor microenvironment, both of which are embedded in the extracellular matrix (ECM). The acquisition of resistance to detachment-induced apoptosis, also known as anoikis, is a critical step in the metastatic cascade. Thus, a more in-depth and systematic analysis is needed to identify the key drivers of anoikis resistance. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…Recently, it has been found that PCMT1 is involved in tumor development and progression, and might be a potential biomarker for diagnosis or prognosis of several tumors. For example, PCMT1 expression was signi cantly higher in hepatocellular carcinoma, bladder cancer, advanced-stage lung adenocarcinoma and metastatic ovarian cancer, and higher PCMT1 expression predicted poor prognosis of above malignant tumors [6,7,11,23]. Up to now, although it has showed that PCMT1 mRNA was highly expressed in BC, and the survival of BC patient with higher expression of PCMT1 was signi cantly poorer than those with lower expression [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been found that PCMT1 is involved in tumor development and progression, and might be a potential biomarker for diagnosis or prognosis of several tumors. For example, PCMT1 expression was signi cantly higher in hepatocellular carcinoma, bladder cancer, advanced-stage lung adenocarcinoma and metastatic ovarian cancer, and higher PCMT1 expression predicted poor prognosis of above malignant tumors [6,7,11,23]. Up to now, although it has showed that PCMT1 mRNA was highly expressed in BC, and the survival of BC patient with higher expression of PCMT1 was signi cantly poorer than those with lower expression [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…The latest research showed that PCMT1 promoted the migration and invasion ability of glioblastoma cells and plays a critical role in the development of glioblastoma [25,26]. Through binding with LAMB3, PCMT1 activated integrin-FAK-Src signaling to enhance ovarian cancer cell adhesion, migration, invasion and metastasis formation [11]. PCMT1 also participated in bladder cancer cell migration and invasion by regulating epithelial-mesenchymal transition-related genes [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin β1/LRRC15 exerts a metastatic invasion role via activation of FAK in patient-derived ovarian cancer xenograft models, inhibited by ABBV-085, an antibody–drug conjugate of LRRC15 ( 195 ). Following binding to integrin, PCMT1 was released from ovarian cancer cells, leading to activated FAK-Src signaling to promote cancer progression and anoikis resistance ( 196 ). Moreover, stiffness-induced autophagy in stromal cells mediated by integrin αV-PTK-AMPKα promotes the growth of adjacent pancreatic stellate cells in vitro and in vivo ( 197 ).…”
Section: Integrin and Endocrine-related Cancersmentioning
confidence: 99%
“…Zhang et al, thanks to genome wide CRISPR/Cas9 knockout screen, have identified critical drivers of anoikis, using ovarian cancer cell lines in ultra-low attachment conditions as a model that mimics the situation in which cancer cells shed from the primary attachment. They demonstrated that knockout of Protein-L-Isoaspartate (D-Aspartate) O-methyltransferase ( PCMT1 ), the main driver in anoikis resistance that they identified, caused an increased apoptosis of SKOV3 cells in response to detachment from the ECM, which is correlated with a decreased tumorigenesis and metastasization in the xenograft model [ 110 ].…”
Section: Crispr and Cancermentioning
confidence: 99%